16S rRNA barcoding technique for species identification of processed sea cucumbers from selected Malaysian markets - Kamarudin Kamarul Rahim, Mohamed Rehan Maryam, Mohd Noor Hanina, Ramly Nur Zazarina, Mohamed Rehan Aisyah, (Universiti Pendidikan Sultan Idris, 2016)
16S rRNA barcoding technique for species identification of processed sea cucumbers from selected Malaysian markets by Kamarudin Kamarul Rahim, Mohamed Rehan Maryam, Mohd Noor Hanina, Ramly Nur Zazarina, Mohamed Rehan Aisyah,